Serum Levels of IL-10 and IL-17A in Occult HBV-Infected South-East Iranian Patients - Arababadi, Mohammad Kazemi (Kowsar, 2010)
BACKGROUND AND AIMS: Occult hepatitis B infected (OBI) patients can not completely eradicate hepatitis B virus-DNA (HBV-DNA) from their liver and peripheral blood. The main aim of this study was to investigate the Interleukin (IL)-10and IL-17A serum levels in patients suffering from OBI. MATERIAL AND METHODS: In this observational study, plasma samples of 3700 blood donors were tested for hepatitis Bsurface antigen (HBsAg) and antibodies to the hepatitis B core antigen (anti-HBc), using enzyme-linked immunosorbent assay (ELISA). The HBsAg-/anti-HBc+ samples were selected and screened for HBV-DNA, using the polymerase chain reaction (PCR). HBV-DNA positive samples were assigned as OBI cases and IL-10 and IL-17 serum levels were detected using ELISA. RESULTS: The results demonstrated that, 352 (9.5%) out of 3700 blood samples were HBsAg-/anti-HBc+ and HBV-DNA was detected in 57/352 (16.1%) of the HBsAg-/anti-HBc+ samples. Our results showed that the IL-10 and IL-17A serum levels increased significantly in the OBI cases in comparison to the controls (P < 0.001). CONCLUSIONS: According to the results of this study the higher level of IL-10 production may suppress the functioning of the immune system against HBV in OBI patients. The elevated IL-17A serum level also indicates a long period of infection in the patients observed.